Catalytic effect of Ag embedded with ZnO prepared by Co-sputtering on H2S gas sensing MEMS device. (August 2022) - Chou, Cheng-Hsueh; Nagarjuna, Yempati; Yang, Zong-Cheng; Hsiao, Yu-Jen; Wang, Sheng-Chang
Abstract: Ag doped ZnO thin films are deposited on a micro electromechanical systems (MEMS) device incorporating a microheater and sensing electrodes using a co-sputtering system. Structural properties and sensing properties were tested with pure Zn alongside with 0.15%, 0.3%, 0.5%, 1% and 2% Ag doping concentrations. The H2 S gas sensing performance of the MEMS-based devices is evaluated for H2 S concentrations in the range of 0.2–1.0 ppm and heating temperatures of 150–300 °C. The optimal sensing performance is obtained with a Ag concentration of 0.5% and a working temperature of 250 °C. For an H2 S gas concentration of 1 ppm, the sensor achieves a sensing response of 16% and a response time of 3 s. The sensor additionally shows good selectivity for H2 S gas compared to that for CO, NO2, NH3 and SO2, respectively. Finally, different response time phenomenon is explained due to the formation of Ag + on doped ZnO surface. Highlights: Co-sputtering process was used to prepare ZnO samples with different Ag doping concentrations. The 3D MEMS heating structure improves the uniformity of heat conduction. As the concentration of silver-doped zinc oxide increases, the morphology of film structure changes. Through the silver-doped zinc oxide film, the gas sensor's catalytic diffusion and saturation reaction mechanism for H2 S gas is changed.